2006
DOI: 10.1348/000712605x70066
|View full text |Cite
|
Sign up to set email alerts
|

The effect of word and character frequency on the eye movements of Chinese readers

Abstract: Eye movements of native Chinese readers were monitored as they read sentences containing target words that varied in terms of word frequency and character frequency. There was an effect of word frequency on fixation times on a target word and it was comparable in size to that typically found with readers of English. Furthermore, character frequency also influenced fixation time on the target word. The effect of the initial character in two character words was more pronounced than that of the second character. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

38
166
8
3

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 158 publications
(215 citation statements)
references
References 14 publications
38
166
8
3
Order By: Relevance
“…Low-frequency words were fixated longer and were less likely to be skipped, which is consistent with the results of previous studies (Tsai & McConkie, 2003;G. Yan et al, 2006;H.-M. Yang & McConkie, 1999).…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…Low-frequency words were fixated longer and were less likely to be skipped, which is consistent with the results of previous studies (Tsai & McConkie, 2003;G. Yan et al, 2006;H.-M. Yang & McConkie, 1999).…”
Section: Resultssupporting
confidence: 91%
“…(1) For visual complexity (in terms of number of strokes), words composed of complicated characters were skipped less often and/or fixated longer than were words composed of less complicated characters (H.-M. Yang & McConkie, 1999). (2) For lexical frequency, fixation durations on high-frequency words and words with high-frequency constituent characters were shorter than fixation durations on low-frequency counterparts (G. Yan, Tian, Bai, & Rayner, 2006;H.-M. Yang & McConkie, 1999). Moreover, the character frequency effect was modulated by word frequency, being evident when word frequency was low but negligible when it was high.…”
mentioning
confidence: 98%
“…In particular, words which have a low frequency of usage, and so are seldom encountered in written Chinese, are more likely to be fixated, and fixated for longer, than higher frequency words (e.g., Liversedge, Zang, Zhang, Bai, Yan, & Drieghe, 2014;Yan, Tian, Bai, & Rayner, 2006;Yang & McConkie, 1999). In addition, because Chinese characters occupy the same area of space, yet are created from a differing number of character strokes, their visual complexity varies.…”
Section: Eye Movements and Ageing In Chinese Readingmentioning
confidence: 99%
“…Words with highfrequency characters were identified more quickly and accurately than words with lowfrequency characters. Yan, Tian, Bai, and Rayner (2006) independently varied the frequency of a target word and the characters composing it during a sentence reading task. Results showed that both word frequency and character frequency influenced the processing of the fixated word in first-pass reading times.…”
Section: N+2 Preview Effectsmentioning
confidence: 99%